1992
DOI: 10.1161/01.hyp.19.6.734
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-adrenergic receptors and 45Ca2+ efflux in arteries from deoxycorticosterone acetate hypertensive rats.

Abstract: Increased vascular sensitivity to catecholamines characterizes mineralocorticoid hypertension. The present study investigated three possible sites that may account for this abnormality: agonist affinity, Ca 2+ release from intracellular stores, and Ca 2+ sensitivity of the contractile proteins. Adult male Sprague-Dawley rats underwent uninephrectomy and were implanted subcutaneously with deoxycorticosterone acetate (DOCA; 200 mg/kg, 1% NaC10.2% KC1 drinking water, 4-6 weeks). Control rats were sham treated. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The increased sensitivity in the hypertensive vasculature has been proposed to be due to increased phosphoinositide metabolism, increased number of receptors, and possibly increased efflux of sarcoplasmic reticulum calcium [35,39,40].…”
Section: Increased Vasoconstrictor Sensitivity In Hypertensionmentioning
confidence: 99%
“…The increased sensitivity in the hypertensive vasculature has been proposed to be due to increased phosphoinositide metabolism, increased number of receptors, and possibly increased efflux of sarcoplasmic reticulum calcium [35,39,40].…”
Section: Increased Vasoconstrictor Sensitivity In Hypertensionmentioning
confidence: 99%
“…Both the Na ϩ content and passive flux of Na ϩ are increased in vascular smooth muscle from mineralocorticoid-treated animals, 5,7 and both the mRNA and activity of the Na ϩ pump are increased. [7][8][9][10] This upregulation of the Na ϩ pump is probably secondary to increased Na ϩ influx because intracellular [Na ϩ ] is increased rather than decreased. 5,11 Although increased intracellular [Na ϩ ] could stimulate Ca influx through the Na-Ca exchange, thereby increasing contractility, Ca stores do not appear to be increased in vascular smooth muscle from mineralocorticoid-treated rats.…”
mentioning
confidence: 99%
“…We found that the vasoconstrictor response to KCl was significantly increased in endothelium-denuded aortic rings from DOCA-salt treated rats as compared to that from control group. No changes in calcium sensitivity have been shown in arteries [17] from mineralocorticoidsalt hypertensive rats. So, a greater increase in extracellular calcium influx evoked by KCl may account for its enhanced contractile response in DOCA-salt rats.…”
Section: Discussionmentioning
confidence: 92%